The impact of highly active antiretroviral therapy on obstetric conditions: A review. (March 2017) - Sebitloane, Hannah M.; Moodley, Dhayendre
Abstract: HIV is the leading cause of maternal and neonatal morbidity and mortality in resource constrained countries. Highly active antiretroviral treatment (HAART) initiated in pregnancy has now almost eliminated mother to child transmission of the virus, and is beginning to show the desired effect of reducing HIV related maternal mortality. By modulating host immunological responses HAART has the potential to alter infections during pregnancy, in addition to modifying clinical conditions such as preeclampsia. There is increasing evidence of the benefits of HAART given to pregnant women, however there is paucity of data that distinguishes HIV or HAART as the cause or exacerbation of pre-existing medical conditions or conditions specific to pregnancy. Anaemia is the commonest haematological disorder seen in HIV infected women and is more pronounced during pregnancy. The use of HAART has the potential to reduce the incidence and severity of the disease. Tuberculosis (TB) is the commonest chest infection amongst HIV infected people, being more common amongst pregnant than non-pregnant women. It is the leading cause of death from infectious diseases amongst women of reproductive age, and accounts for at least a quarter of all cases of maternal deaths associated with non-pregnancy related infections (NPRI). TB can manifest at any stage of the HIV infection, including during treatment with HAART. The latter (ie TB manifestation during HAART treatment) is thought to be the commonest manifestation of what is now known as immune reconstitution inflammatory syndrome (IRIS). In a South African report on maternal deaths, 55% of women who died of TB were on HAART, and a further 35% of women in the NPRI category died from other pneumoniae, notably pneumocystis jorevicci, which is also related to HIV infection. With regards to puerperal sepsis, studies are yet to show the impact of HAART independent of antibiotics in reducing infectious morbidity in HIV infected women. Preeclampsia has been associated with HIV infection, where most studies point towards a reduced risk in HIV infected women. There is increasing evidence that this reduced risk is reversed in the presence of HAART, with women accessing HAART having almost the same risk as HIV uninfected women. HIV or its treatment may be associated with increased risk of obstetric haemorrhage, and an increasing trend of obstetric haemorrhage as a cause of maternal deaths has been recently reported, proportionally in line with the introduction and increasing availability of HAART for pregnant women The mechanism by which this may occur remains elusive since pregnancy is a pro-thrombotic state, however, HIV-related thrombocytopenia or vasculitis could account for the association, if found. HAART would then be expected to reverse this. HAART especially protease inhibitor containing combinations, have been associated with preterm deliveries and low birth weight, particularly when initiated prior to the index pregnancy. With these overall findings of the effect of HAART on obstetric conditions, this review is intended to encourage heightened surveillance of adverse events associated with HAART use in pregnant women.